2011
DOI: 10.1111/j.1948-7134.2011.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of phlebotomine sand flies in the Aydin Mountains and surroundings: the main focus of cutaneous leishmaniasis in western Turkey

Abstract: An entomological survey was conducted to determine the spatial distribution of phlebotomine fauna and understand the effect of environmental factors. The entomological survey was carried out during 2006-2007 in a study area in the rural area of Aydin province, near the Kusadasi town where VL, CL, and canine leishmaniasis (CanL) are endemic. In 2006 and 2007, 132 locations were sampled using sticky traps mainly on embankments. Detailed environmental and meteorological information was also collected for each loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
(30 reference statements)
1
28
0
2
Order By: Relevance
“…Several studies have recently reported the influence of environmental and climatic conditions on the distribution of leishmaniasis vectors (Rossi et al, 2007;Gálvez et al, 2010a;Ozbel et al, 2011;Queiroz et al, 2012;Branco et al, 2013). This study is the first to show the effect of these variables separately on P. ariasi and P. perniciosus living in sympatric conditions when captured with sticky traps in a given region showing a great variation of environmental conditions.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Several studies have recently reported the influence of environmental and climatic conditions on the distribution of leishmaniasis vectors (Rossi et al, 2007;Gálvez et al, 2010a;Ozbel et al, 2011;Queiroz et al, 2012;Branco et al, 2013). This study is the first to show the effect of these variables separately on P. ariasi and P. perniciosus living in sympatric conditions when captured with sticky traps in a given region showing a great variation of environmental conditions.…”
Section: Discussionmentioning
confidence: 60%
“…The abundance of sand fly species was estimated as densities (number of sand flies per m 2 trap) (Gálvez et al, 2010a;Ozbel et al, 2011). The factors and categories considered are shown in the appendix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence that P. papatasi and P. sergenti are specific vectors for L. major and L. tropica respectively (Dostalova and Volf, 2012) and not involved in the transmission of L. infantum. P. similis is also a suspected vector of L. tropica, although the role of this species has yet to be proven (Christodoulou et al, 2012, Ozbel et al, 2011. Figure 32a.…”
Section: Supporting Publications 2013:en-466 109mentioning
confidence: 99%